A modified organic silicon material and rubber composition for new energy vehicle tires

By using modified silicone materials and rubber compositions in new energy vehicle tires, the problem of tire heat generation is solved, the thermal conductivity and wear resistance are improved, and the service life is extended.

CN118879084BActive Publication Date: 2025-03-07SHANDONG HUASHENG RUBBER +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411201538.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2025-03-07
Estimated Expiration
2044-08-29

AI Technical Summary

Technical Problem

The prior art is difficult to effectively reduce the heat generation problem of tires in new energy vehicles, resulting in tire tread delamination, intensification of internal aging, and shortening of service life.

Method used

Using modified silicone materials and rubber compositions, the thermal conductivity and heat resistance of the tire are improved and the use of carbon black is reduced by introducing vinyl-terminated siloxane polymers, white carbon black, silane coupling agents and acrylates.

Benefits of technology

It effectively reduces the heat generation of the tire, improves thermal conductivity and wear resistance, extends service life, and improves the strength and aging resistance of the tire.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005017963890000111
    Figure BDA0005017963890000111
  • Figure BDA0005017963890000121
    Figure BDA0005017963890000121
  • Figure BDA0005017963890000131
    Figure BDA0005017963890000131
Patent Text Reader

Abstract

The present invention provides a modified organic silicon material and a rubber composition for new energy vehicle tires, and relates to the technical field of tires. The present invention uses vinyl-terminated siloxane polymers, white carbon black, diatomaceous earth, silane coupling agents, and acrylates as raw materials to prepare modified organic silicon materials for new energy vehicle tires. The obtained modified organic silicon material has the characteristics of good compatibility with rubber components, high mechanical properties, and good heat resistance. When used to prepare rubber tires, it can improve the mechanical properties and wear resistance of the tires, reduce heat generation, improve thermal conductivity, and improve aging resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of tire technology, and in particular to a modified organic silicon material and a rubber composition for new energy vehicle tires. Background Art

[0002] Electric vehicles have outstanding advantages such as low noise, zero emissions, and comprehensive utilization of energy. They are an important way to solve energy and environmental problems and are becoming the development trend of future vehicles. As the only part of a car that contacts the ground, the performance of tires directly affects the safety, stability, and economy of electric vehicles. Therefore, the market has higher and higher requirements for tires. During the rolling process of tires, rubber materials have to undergo large-scale and high-frequency repeated deformations, which will generate a lot of heat. The temperature rise can easily cause problems such as tire tread delamination and internal aging, which will reduce the service life of the tire.

[0003] There are several ways to solve the problem of tire heating. The first is to reduce tire heating, which can be achieved by selecting low-heat rubber components. The large amount of carbon black used will cause the tire to generate a lot of heat and increase the rolling resistance of the tire. Therefore, by introducing other low-heat fillers to reduce the use of filler carbon black, it can also effectively reduce the problem of tire heating. The second is to improve the heat resistance of tire rubber, which can be achieved by selecting appropriate antioxidants. The third is to improve the thermal conductivity of tire rubber, which can be achieved by selecting appropriate thermal conductive fillers.

[0004] At present, the industry mostly uses white carbon black to reduce heat generation, and has achieved certain results. Although using white carbon black instead of carbon black can reduce heat generation, the reinforcement effect of white carbon black is not as good as that of carbon black, and the dispersibility of white carbon black is poor. The use of silane coupling agent can improve the dispersibility of white carbon black to a certain extent, but the interaction between white carbon black and rubber is still insufficient. In addition, the thermal conductivity of white carbon black is poor, and the problem of using white carbon black to reduce tire heat generation has not been well solved. Therefore, how to solve the problem of heat generation and heat conduction of tires and improve their service life is still the focus of research and development in this field. Summary of the invention

[0005] In view of the above situation, in order to make up for the defects of the prior art, the present invention provides a modified silicone material and rubber composition for new energy vehicle tires, which at least solves some of the problems existing in the prior art.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] On the one hand, a modified organic silicon material for new energy vehicle tires comprises the following raw materials in parts by weight:

[0008] 100 parts of vinyl-terminated siloxane polymer, 10-20 parts of white carbon black, 2-5 parts of silane coupling agent, and 3-10 parts of ethyl acrylate; wherein,

[0009] The silane coupling agent comprises a vinyl-containing silane coupling agent and a mercapto-containing silane coupling agent in a mass ratio of 1:(1-2.5).

[0010] Preferably, the modified organic silicon material for new energy vehicle tires comprises the following raw materials in parts by weight: 100 parts of vinyl-terminated siloxane polymer, 15 parts of white carbon black, 3 parts of silane coupling agent, and 6 parts of ethyl acrylate.

[0011] Preferably, the silane coupling agent comprises a vinyl-containing silane coupling agent and a mercapto-containing silane coupling agent in a mass ratio of 1:1.8.

[0012] Furthermore, the vinyl-containing silane coupling agent is selected from at least one of vinyl trimethoxy silane, vinyl triethoxy silane and vinyl (β-methoxyethoxy) silane.

[0013] Furthermore, the mercapto-containing silane coupling agent is selected from at least one of mercaptopropyltrimethoxysilane, mercaptopropyltriethoxysilane, mercaptopropylmethyldimethoxysilane and mercaptopropylmethyldiethoxysilane.

[0014] Furthermore, the acrylic acid ester is selected from at least one of methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate and butyl acrylate.

[0015] Furthermore, the vinyl-terminated siloxane polymer is prepared by polymerization of tetramethyldivinyldisiloxane and octamethylcyclotetrasiloxane; wherein the mass ratio of tetramethyldivinyldisiloxane to octamethylcyclotetrasiloxane is 1:(3-5).

[0016] Preferably, the vinyl terminated siloxane polymer is prepared by the following method:

[0017] Tetramethyldivinyldisiloxane and octamethylcyclotetrasiloxane are added into a reaction kettle in proportion, a catalyst is added, the reaction is carried out at 80-100°C for 6-8h, the temperature is reduced to below 50°C, filtered, and distilled under reduced pressure to obtain a vinyl-terminated siloxane polymer.

[0018] More preferably, the catalyst is concentrated sulfuric acid, and the amount of the catalyst used is 1 to 5% of the total mass of the reactants.

[0019] On the other hand, the method for preparing the modified organic silicon material for new energy vehicle tires comprises the following steps:

[0020] The white carbon black is treated with a vinyl-containing silane coupling agent and an acrylate in sequence, and then a vinyl-terminated siloxane polymer and a mercapto-containing silane coupling agent are added and mixed evenly, and finally a catalyst is added to react. After the reaction is completed, the modified organic silicon material for new energy vehicle tires is obtained.

[0021] Furthermore, the specific steps of treating the white carbon black with a vinyl-containing silane coupling agent and an acrylate in sequence are:

[0022] Mix the vinyl silane coupling agent with 8-10 times the mass of water and ethanol, add white carbon black and ultrasonically treat for 0.5-1h, take out and dry after the reaction, then put it into 10-15 times the mass of ethanol, add acrylate, react at 70-80°C for 3-5h, take out and dry after the reaction.

[0023] Preferably, the mass ratio of water to ethanol is (6-8):(2-4).

[0024] Preferably, the ultrasonic treatment is performed at an ultrasonic power of 200 to 400W.

[0025] Furthermore, in step S2, the catalyst is selected from a titanate catalyst; and the amount of the catalyst used is 0.1 to 0.5% of the total mass of the reactants.

[0026] Furthermore, in step S2, the solvent is selected from at least one of toluene, tetrahydrofuran, dichloromethane and petroleum ether.

[0027] Furthermore, in step S2, the reaction temperature is 110-120° C. and the reaction time is 1-3 h.

[0028] On the other hand, a rubber composition for new energy vehicle tires comprises a rubber component and the aforementioned modified silicone material; in 100 parts by weight of the rubber component, the aforementioned modified silicone material accounts for 20 to 30 parts by weight, preferably 24 parts by weight.

[0029] Furthermore, the rubber component for new energy vehicle tires comprises natural rubber, neodymium-based butadiene rubber and solution-polymerized styrene-butadiene rubber in a mass ratio of (10-15):(20-30):(55-70); preferably, the rubber component comprises natural rubber, neodymium-based butadiene rubber and solution-polymerized styrene-butadiene rubber in a mass ratio of 12:26:62.

[0030] Furthermore, the rubber composition for new energy vehicle tires also contains carbon black, a vulcanizing agent, a vulcanization accelerator and an antioxidant; relative to 100 parts by weight of the rubber component, the carbon black is 5 to 10 parts by weight, the vulcanizing agent is 1 to 3 parts by weight, the vulcanization accelerator is 0.2 to 2 parts by weight, and the antioxidant is 2.5 to 5 parts by weight.

[0031] Preferably, in the rubber composition for new energy vehicle tires, relative to 100 parts by weight of the rubber component, the carbon black is 7 parts by weight, the vulcanizing agent is 1.5 parts by weight, the vulcanization accelerator is 0.5 parts by weight, and the antioxidant is 3 parts by weight.

[0032] Preferably, the vulcanizing agent is sulfur.

[0033] Preferably, the vulcanization accelerator is selected from at least one of sulfonamide accelerators, diphenylguanidine accelerators, and thiuram accelerators, including but not limited to at least one of N-tert-butyl-2-benzothiazole sulfenamide, N-cyclohexyl-2-benzothiazole sulfenamide, N,N′-dicyclohexyl-2-benzothiazole sulfenamide, and tetrabenzylthiuram disulfide.

[0034] Preferably, the antioxidant is a p-phenylenediamine antioxidant, including but not limited to any one or a combination of two of N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine and N,N'-xylyl-p-phenylenediamine.

[0035] In a further embodiment, the tire further comprises esterified lignocellulose, and the esterified lignocellulose is 3 to 8 parts by weight relative to 100 parts by weight of the rubber component. The esterified lignocellulose is prepared by esterification reaction of lignocellulose with maleic anhydride and palmitic anhydride; the mass ratio of lignocellulose to maleic anhydride and palmitic anhydride is 10:(5 to 7):(0.5 to 1).

[0036] Preferably, the esterified lignocellulose is prepared by the following method:

[0037] Dissolve maleic anhydride and palmitic anhydride in 2-3 times the mass of DMF, add lignocellulose, add 1-2% of the total mass of anhydride as a catalyst hydroquinone, stir and react at 90-110° C. for 3-5 hours, filter and dry after the reaction to obtain the esterified lignocellulose.

[0038] On the other hand, the method for preparing the rubber composition for new energy vehicle tires comprises the following steps:

[0039] S1. Mixing the rubber component, the modified organic silicon material for new energy vehicle tires and carbon black, and cooling at room temperature after mixing to obtain an initial masterbatch;

[0040] S2, mixing the antioxidant, esterified lignocellulose and the initial masterbatch, and cooling at room temperature after mixing to obtain a mixed rubber;

[0041] S3, mixing the mixed rubber with the vulcanizing agent and the vulcanization accelerator, draining the rubber, cooling the sheet, and obtaining the final mixed rubber. Further, in step S1, the mixing temperature is 130-150°C, the time is 60-120s; the room temperature cooling time is 4-6h.

[0042] Furthermore, in step S2, the mixing temperature is 130-150°C, and the mixing time is 60-120s; and the room temperature cooling time is 2-6h.

[0043] Furthermore, in step S3, the mixing temperature is 110-130° C., and the mixing time is 100-150 seconds.

[0044] On the other hand, a new energy vehicle tire is prepared from the rubber composition for new energy vehicle tires described above.

[0045] Compared with the prior art, the present invention has the following beneficial effects:

[0046] 1. Compared with traditional silicone resin, the modified silicone material provided by the present invention has the characteristics of good compatibility with rubber components, high mechanical properties and good heat resistance. The use of modified silicone in rubber tires not only makes up for the problem of decreased mechanical properties caused by poor compatibility with rubber components in the prior art, but also improves the mechanical properties. In addition, the addition of modified silicone resin reduces the use of carbon black, reduces heat generation, improves thermal conductivity, improves wear resistance and aging resistance, and extends service life.

[0047] 2. The white carbon black of the present invention is treated with a vinyl-containing silane coupling agent and acrylate and then reacted with other raw materials, thereby increasing the dispersibility of the white carbon black and solving the problem of poor dispersibility of the white carbon black. It can not only effectively reduce the heat generation problem of the rubber tire, but also have a good reinforcement effect and improve the strength of the rubber tire.

[0048] 3. The modified silicone material introduces two coupling agents, vinyl silane coupling agent and mercapto silane coupling agent, and is combined with acrylate to increase the binding property between white carbon black and silicone resin, thereby improving the strength and wear resistance of rubber tires and improving thermal conductivity. It can also make up for the poor aging resistance of silicone resin and improve the aging resistance of silicone resin, thereby improving the aging resistance of rubber tires and increasing service life.

[0049] 4. Esterified lignocellulose is introduced into the rubber composition of the present invention. The hydroxyl groups in the esterified lignocellulose are reduced while the number of ester carbon chains is increased, thereby reducing the polarity of the lignocellulose and improving the compatibility with the rubber component, which helps to improve the strength and wear resistance of the rubber tire, increase the thermal conductivity, and improve the aging resistance. DETAILED DESCRIPTION

[0050] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. The following content is only an exemplary description of the scope of the present invention, and those skilled in the art can make various changes and modifications to the invention of the present invention based on the disclosed content, and they should also fall within the scope of the present invention.

[0051] The present invention is further described below by way of specific examples. Unless otherwise specified, the various chemical reagents used in the examples of the present invention are obtained through conventional commercial channels.

[0052] Example 1

[0053] This embodiment provides a modified organic silicon material for new energy vehicle tires, which is prepared by the following method:

[0054] (1) Raw material preparation: 100 g of vinyl-terminated siloxane polymer, 10 g of white carbon black, 2 g of silane coupling agent (vinyltrimethoxysilane and mercaptopropyltrimethoxysilane in a mass ratio of 1:1), and 3 g of methyl acrylate.

[0055] Among them, the vinyl-terminated siloxane polymer is prepared by the following method: tetramethyldivinyldisiloxane and octamethylcyclotetrasiloxane are added into a reaction kettle in a mass ratio of 1:3, concentrated sulfuric acid is added in an amount of 5% of the total mass of the reactants, reacted at 100°C for 6 hours, cooled to below 50°C, filtered, and distilled under reduced pressure to obtain a vinyl-terminated siloxane polymer.

[0056] (2) Vinyl trimethoxysilane is mixed with 8 times the mass of water and ethanol (mass ratio 8:2), white carbon black is added and ultrasonically treated for 1 hour, the ultrasonic power is 300 W, and after the reaction, the mixture is taken out and dried, and then put into 10 times the mass of ethanol, methyl acrylate is added, and the mixture is reacted at 70° C. for 5 hours, and after the reaction, the mixture is taken out and dried; then the mixture is added into toluene, and then vinyl-terminated siloxane polymer and mercaptopropyl trimethoxysilane are added and mixed, and finally 0.5% of the total mass of the reactants is added into butyl titanate for reaction, and after the reaction, the modified organic silicon material for new energy vehicle tires is obtained.

[0057] This embodiment also provides a rubber composition, which is prepared by the following method:

[0058] S1. Raw material preparation:

[0059] Rubber components: 10g natural rubber, 20g neodymium-based butadiene rubber, 70g solution-polymerized styrene-butadiene rubber; 20g modified silicone material for new energy vehicle tires, 10g carbon black, 1g sulfur, 0.2g vulcanization accelerator N-tert-butyl-2-benzothiazole sulfonamide, and 2.5g antioxidant N,N'-xylyl p-phenylenediamine.

[0060] S2, mixing the rubber component, the modified silicone material for new energy vehicle tires and carbon black at a mixing temperature of 130° C. for 120 seconds, and cooling at room temperature for 4 hours after mixing to obtain an initial masterbatch;

[0061] S3, mixing the antioxidant with the initial masterbatch at a mixing temperature of 130° C. for 120 seconds, cooling at room temperature for 2 hours after mixing, and obtaining a mixed rubber;

[0062] S4, mixing the mixed rubber with sulfur and vulcanization accelerator at a temperature of 110°C for 150 seconds, draining the rubber, cooling the sheet, and obtaining the final mixed rubber.

[0063] Example 2

[0064] This embodiment provides a modified organic silicon material for new energy vehicle tires, which is prepared by the following method:

[0065] (1) Raw material preparation: 100 g of vinyl-terminated siloxane polymer, 15 g of white carbon black, 3 g of silane coupling agent (vinyl triethoxysilane and mercaptopropyl triethoxysilane in a mass ratio of 1:1.8), and 6 g of ethyl acrylate.

[0066] Among them, the vinyl-terminated siloxane polymer is prepared by the following method: tetramethyldivinyldisiloxane and octamethylcyclotetrasiloxane are added into a reaction kettle in a mass ratio of 1:4, concentrated sulfuric acid is added in an amount of 5% of the total mass of the reactants, reacted at 100°C for 6h, cooled to below 50°C, filtered, and distilled under reduced pressure to obtain a vinyl-terminated siloxane polymer.

[0067] (2) Vinyl triethoxysilane is mixed with 8 times the mass of water and ethanol (mass ratio 8:2), white carbon black is added and ultrasonically treated for 1 hour, the ultrasonic power is 300 W, and after the reaction, the mixture is taken out and dried, and then put into 10 times the mass of ethanol, ethyl acrylate is added, and the mixture is reacted at 70° C. for 5 hours, and after the reaction, the mixture is taken out and dried; then the mixture is added into toluene, and then vinyl-terminated siloxane polymer and mercaptopropyl triethoxysilane are added and mixed, and finally 0.5% of the total mass of the reactants is added into butyl titanate for reaction, and after the reaction, the modified organic silicon material for new energy vehicle tires is obtained.

[0068] This embodiment also provides a rubber composition, which is prepared by the following method:

[0069] S1. Raw material preparation:

[0070] Rubber components: 12g natural rubber, 26g neodymium-based butadiene rubber, 62g solution-polymerized styrene-butadiene rubber; 24g modified silicone material, 7g carbon black, 1.5g sulfur, 0.5g vulcanization accelerator N-tert-butyl-2-benzothiazole sulfonamide, 3g antioxidant N,N'-xylyl-p-phenylenediamine.

[0071] S2, mixing the rubber component, the modified silicone material and the carbon black at a temperature of 140° C. for 100 seconds, and cooling at room temperature for 6 hours after mixing to obtain an initial masterbatch;

[0072] S3, mixing the antioxidant with the initial masterbatch at a mixing temperature of 150° C. for 100 seconds, cooling at room temperature for 4 hours after mixing, and obtaining a mixed rubber;

[0073] S4, mixing the mixed rubber with sulfur and vulcanization accelerator at a temperature of 120°C for 120 seconds, draining the rubber, cooling the sheet, and obtaining the final mixed rubber.

[0074] Example 3

[0075] This embodiment provides a modified organic silicon material for new energy vehicle tires, which is prepared by the following method:

[0076] (1) Raw material preparation: 100 g of vinyl-terminated siloxane polymer, 20 g of white carbon black, 5 g of silane coupling agent (vinyl triethoxysilane and mercaptopropyl triethoxysilane in a mass ratio of 1:2.5), and 10 g of ethyl acrylate.

[0077] Among them, the vinyl-terminated siloxane polymer is prepared by the following method: tetramethyldivinyldisiloxane and octamethylcyclotetrasiloxane are added into a reaction kettle in a mass ratio of 1:5, concentrated sulfuric acid is added in an amount of 5% of the total mass of the reactants, reacted at 100°C for 6h, cooled to below 50°C, filtered, and distilled under reduced pressure to obtain a vinyl-terminated siloxane polymer.

[0078] (2) Vinyl triethoxysilane is mixed with 8 times the mass of water and ethanol (mass ratio 8:2), white carbon black is added and ultrasonically treated for 1 hour, the ultrasonic power is 300 W, the time is 0.5 hour, and after the reaction, the mixture is taken out and dried, and then put into 10 times the mass of ethanol, ethyl acrylate is added, and the mixture is reacted at 70° C. for 5 hours. After the reaction, the mixture is taken out and dried; then the mixture is added into toluene, and then vinyl-terminated siloxane polymer and mercaptopropyl triethoxysilane are added and mixed, and finally 0.5% of the total mass of the reactants is added into butyl titanate for reaction, and after the reaction, the modified organic silicon material for new energy vehicle tires is obtained.

[0079] This embodiment also provides a rubber composition, which is prepared by the following method:

[0080] S1. Raw material preparation:

[0081] Rubber components: 15g natural rubber, 30g neodymium-based butadiene rubber, 55g solution-polymerized styrene-butadiene rubber; 30g modified silicone material, 5g carbon black, 3g sulfur, 2g vulcanization accelerator N-tert-butyl-2-benzothiazole sulfonamide, and 5g antioxidant N,N'-xylyl-p-phenylenediamine.

[0082] S2, mixing the rubber component, the modified silicone material and the carbon black at a temperature of 150° C. for 60 seconds, and cooling at room temperature for 6 hours after mixing to obtain an initial masterbatch;

[0083] S3, mixing the antioxidant with the initial masterbatch at a mixing temperature of 150° C. for 60 seconds, cooling at room temperature for 6 hours after mixing, and obtaining a mixed rubber;

[0084] S4, mixing the mixed rubber with sulfur and vulcanization accelerator at a temperature of 130°C for 100 seconds, draining the rubber, cooling the sheet, and obtaining the final mixed rubber.

[0085] Example 4

[0086] The difference from Example 2 is that the rubber composition further comprises 8 g of esterified lignocellulose, and the esterified lignocellulose is added simultaneously with the antioxidant in step S3; wherein the esterified lignocellulose is prepared by the following method:

[0087] According to the mass ratio of lignocellulose to maleic anhydride and palmitic anhydride of 10:5:0.5, maleic anhydride and palmitic anhydride were dissolved in 3 times the mass of DMF, lignocellulose was added, and a catalyst hydroquinone was added in an amount of 2% of the total mass of the anhydride, and the mixture was stirred and reacted at 110° C. for 3 hours. After the reaction was completed, the mixture was filtered and dried to obtain the esterified lignocellulose.

[0088] Example 5

[0089] The difference from Example 4 is that the esterified lignocellulose is prepared by the following method:

[0090] According to the mass ratio of lignocellulose to maleic anhydride and palmitic anhydride of 10:7:1, maleic anhydride and palmitic anhydride were dissolved in 3 times the mass of DMF, lignocellulose was added, and a catalyst hydroquinone was added in an amount of 2% of the total mass of the anhydride, and the mixture was stirred and reacted at 110°C for 3 hours. After the reaction was completed, the mixture was filtered and dried to obtain the esterified lignocellulose.

[0091] Example 6

[0092] The difference from Example 4 is that during the preparation of esterified lignocellulose, the mass ratio of lignocellulose to maleic anhydride and palmitic anhydride is 10:4:1.5.

[0093] Example 7

[0094] The difference from Example 4 is that during the preparation of esterified lignocellulose, the mass ratio of lignocellulose to maleic anhydride and palmitic anhydride is 10:8:0.2.

[0095] Example 8

[0096] The difference from Example 4 is that the esterified lignocellulose is prepared by the following method:

[0097] According to the mass ratio of cellulose to maleic anhydride of 10:8, maleic anhydride was dissolved in 3 times the mass of DMF, added to cellulose, and added with catalyst hydroquinone which was 2% of the total mass of the anhydride, and stirred at 110° C. for 3 hours. After the reaction was completed, the esterified cellulose was obtained by filtering and drying.

[0098] Comparative Example 1

[0099] The difference from Example 2 is that the silane coupling agent in this comparative example is vinyltriethoxysilane and mercaptopropyltriethoxysilane in a mass ratio of 1:0.5, and the total amount of the silane coupling agent remains unchanged.

[0100] Comparative Example 2

[0101] The difference from Example 2 is that the silane coupling agent in this comparative example is vinyltriethoxysilane and mercaptopropyltriethoxysilane in a mass ratio of 1:3, and the total amount of the silane coupling agent remains unchanged.

[0102] Comparative Example 3

[0103] The difference from Example 2 is that the silane coupling agent in this comparative example is only vinyltriethoxysilane, and the total amount of the silane coupling agent remains unchanged.

[0104] Comparative Example 4

[0105] The difference from Example 2 is that the silane coupling agent in this comparative example is only mercaptopropyltriethoxysilane, and the total amount of the silane coupling agent remains unchanged.

[0106] Comparative Example 5

[0107] The difference from Example 2 is that no silane coupling agent is added to the modified silicone resin in this comparative example.

[0108] Comparative Example 6

[0109] The difference from Example 2 is that the modified silicone resin in this comparative example is prepared by the following method:

[0110] Vinyl triethoxysilane, white carbon black, ethyl acrylate, vinyl-terminated siloxane polymer and mercaptopropyl triethoxysilane are added to toluene, and finally 0.5% of the total mass of butyl titanate is added to react. After the reaction is completed, the modified organic silicon material for new energy vehicle tires is obtained.

[0111] Comparative Example 7

[0112] The difference from Example 2 is that the modified silicone resin in this comparative example is replaced by an equal amount of white carbon black.

[0113] Test Example 1

[0114] Tensile properties test

[0115] The tensile strength, tensile stress and elongation at break were tested according to the standard GB / T 528-2009, and the tear strength was tested according to the standard GB / T529-2008. The results are shown in Table 1 below.

[0116] Table 1

[0117]

[0118]

[0119] As shown in the table, compared with the comparative example 7 in which only white carbon black is added, the tensile strength and tear strength of the rubber mix prepared in the embodiment of the present invention are significantly improved. It can be seen that the addition of the modified organosilicon material provided by the present invention makes up for the defect in the prior art that the mechanical properties of the rubber material decrease due to the addition of white carbon black. Compared with Example 2, the rubber mixes in Examples 4 and 5 are further improved by adding esterified wood cellulose. Compared with Example 2, the tensile strength and tear strength of Comparative Examples 1-6 are significantly reduced, indicating that the components in the modified organosilicon material cooperate with each other, which helps to improve the mechanical properties of the rubber mix.

[0120] Test Example 2

[0121] Wear resistance test

[0122] According to GB / T 1689-2014 standard, the Akron abrasion test was carried out using an abrasion instrument. The results are shown in Table 2 below.

[0123] Table 2

[0124] Group <![CDATA[Abrasion loss, cm 3 > Group <![CDATA[Akron abrasion, cm 3 > Example 1 0.19 Comparative Example 1 0.25 Example 2 0.16 Comparative Example 2 0.23 Example 3 0.17 Comparative Example 3 0.22 Example 4 0.11 Comparative Example 4 0.26 Example 5 0.12 Comparative Example 5 0.32 Example 6 0.17 Comparative Example 6 0.24 Example 7 0.16 Comparative Example 7 0.38 Example 8 0.18 —— ——

[0125] As shown in the table, compared with the comparative example 7 which only added white carbon black, the modified organic silicon material added in the example has a significantly reduced Akron wear amount, that is, the wear resistance is improved. Compared with Example 2, the wear resistance of comparative examples 5 and 6 is also reduced, which shows that the addition of silane coupling agent in the modified organic silicon material helps to improve the wear resistance of the mixed rubber. It can also be seen that the wear resistance of Examples 4 and 5 is better than that of Example 2, which shows that the addition of esterified wood cellulose helps to further improve the wear resistance of the mixed rubber.

[0126] Test Example 3

[0127] Compression heating test

[0128] Compression heat generation was tested according to standard ASTM D623-07 and the results are shown in Table 3 below.

[0129] Table 3

[0130]

[0131]

[0132] As shown in the table, the rubber mix prepared in the embodiment of the present invention has low compression heat generation and good thermal conductivity. Although the compression heat generation of the rubber mix obtained in Comparative Example 7 is equivalent to that of Example 2, its thermal conductivity is significantly lower than that of Example 2, indicating that although the addition of white carbon black can reduce the heat generation of the rubber mix, the thermal conductivity is relatively poor, and it still cannot effectively solve the problem of reduced service life of the tire due to rolling heat generation.

[0133] Test Example 4

[0134] Aging resistance test

[0135] The heat aging resistance was tested according to GB / T 3512-2014, the test temperature was 100°C, the test time was 72h, and the tensile strength change rate was used to evaluate the aging resistance. The results are shown in Table 4 below.

[0136] Table 4

[0137] Group Tensile strength change rate, % Group Tensile strength change rate, % Example 1 -8.2 Comparative Example 1 -15.6 Example 2 -6.4 Comparative Example 2 -16.3 Example 3 -7.5 Comparative Example 3 -18.7 Example 4 -1.3 Comparative Example 4 -18.1 Example 5 -1.5 Comparative Example 5 -26.6 Example 6 -7.0 Comparative Example 6 -22.5 Example 7 -6.1 Comparative Example 7 -15.7 Example 8 -7.1 —— ——

[0138] As shown in the table, the rubber compound prepared in the embodiment of the present invention has a small decrease in the late tensile strength at 100°C for 72 hours, and has excellent aging resistance. Compared with Example 2, the components of the modified organic silicon material in Comparative Examples 1-6 are changed, and the change in the tensile strength of the obtained rubber compound is significantly higher than that in the embodiment. It can be seen that the components in the modified organic silicon material cooperate with each other, which helps to improve the aging resistance of the rubber compound, making up for the defect that the existing organic silicon material has poor aging resistance and thus causes the aging resistance to decrease when added to the rubber material.

[0139] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A modified silicone material for new energy vehicle tires, characterized in that: Contains the following raw materials by weight: 100 parts of vinyl-terminated siloxane polymer, 10-20 parts of white carbon black, 2-5 parts of silane coupling agent, and 3-10 parts of acrylate; wherein, The silane coupling agent comprises a vinyl-containing silane coupling agent and a mercapto-containing silane coupling agent in a mass ratio of 1: (1-2.5); The vinyl-containing silane coupling agent is selected from at least one of vinyl trimethoxy silane, vinyl triethoxy silane, and vinyl (β-methoxyethoxy) silane; the mercapto-containing silane coupling agent is selected from at least one of mercaptopropyl trimethoxy silane, mercaptopropyl triethoxy silane, mercaptopropyl methyl dimethoxy silane, and mercaptopropyl methyl diethoxy silane; The vinyl terminated siloxane polymer is prepared by polymerization of tetramethyldivinyldisiloxane and octamethylcyclotetrasiloxane; wherein the mass ratio of tetramethyldivinyldisiloxane to octamethylcyclotetrasiloxane is 1:(3-5); The modified organic silicon material for new energy vehicle tires is prepared by the following method: The white carbon black is treated with a vinyl-containing silane coupling agent and an acrylate in sequence, and then a vinyl-terminated siloxane polymer and a mercapto-containing silane coupling agent are added and mixed evenly, and finally a catalyst is added to react, and the product is obtained after the reaction is completed.

2. A rubber composition for new energy vehicle tires, characterized in that: It comprises a rubber component, the modified organic silicon material for new energy vehicle tires according to claim 1, and carbon black, a vulcanizing agent, a vulcanization accelerator and an antioxidant; in 100 parts by weight of the rubber component, the modified organic silicon material for new energy vehicle tires is 20 to 30 parts by weight.

3. The rubber composition for new energy vehicle tire according to claim 2, characterized in that: The rubber component for new energy vehicle tires comprises natural rubber, neodymium-based butadiene rubber and solution-polymerized styrene-butadiene rubber in a mass ratio of (10-15):(20-30):(55-70).

4. The rubber composition for new energy vehicle tire according to claim 2, characterized in that: The rubber composition for new energy vehicle tires further comprises esterified lignocellulose; The esterified lignocellulose is prepared by esterification reaction of lignocellulose with maleic anhydride and palmitic anhydride; The mass ratio of the wood cellulose to maleic anhydride and palmitic anhydride is 10:(5-7):(0.5-1).

5. The method for preparing the rubber composition for new energy vehicle tire according to claim 4, characterized in that: The following steps are involved: S1. Mixing the rubber component, the modified organic silicon material for new energy vehicle tires according to claim 1, and carbon black, and cooling at room temperature after mixing to obtain an initial masterbatch; S2, mixing the antioxidant, esterified lignocellulose and the initial masterbatch, and cooling at room temperature after mixing to obtain a mixed rubber; S3, mixing the mixed rubber with the vulcanizing agent and the vulcanization accelerator, draining the rubber, cooling the sheet, and obtaining the final mixed rubber.

6. A new energy vehicle tire, characterized in that: The rubber composition for new energy vehicle tires is prepared from any one of claims 2 to 4.

Citation Information

Patent Citations

  • Preparation method for high-dispersion deposition white carbon black

    CN105273442A

  • Poly-mercapto compound-containing white carbon black-filled rubber composite material and preparation method thereof

    CN107022126A